"The peace that I wanted, I got": Qualitative insights from patient experiences of SMART DAPPER interventions for major depression and traumatic stress disorders in Kenya. - Monica Getahun; Muthoni A Mathai; Grace Rota; Ammon Allen; Rachel L Burger; Elizabeth Opiyo; Dennis Oluoch; Josyline Wangia; Raphael Wambura; Anne Mbwayo; Peter Muchembre; Raymond R Obura; et al. (Public Library of Science (PLoS), 2024)
SMART DAPPER is an implementation science study responding to mental health treatment gaps for depression and trauma-related disorders in Sub-Saharan Africa (SSA). We report on patient experiences in a study using a Sequential, Multiple Assignment Randomized Trial (SMART) design to test first and second line non-specialist treatment using psychotherapy (Interpersonal Psychotherapy [IPT] or medication (fluoxetine [FLX]), integrated within public sector primary care in western Kenya. An embedded qualitative study conducted in-depth interviews (n = 17) and three (n = 3) focus group discussions with participants (May to October 2021). Audio-recorded interviews were transcribed and translated into English; we deductively and inductively analyzed transcripts guided by grounded theoretical approaches and content analysis. We drew on the health belief model and socio-ecological framework to present findings, including perceived severity (motivations for taking part in the intervention), impacts of the intervention at the individual, interpersonal, and community and health systems levels as well as barriers and facilitators. Participants discussed family and marital conflict, loss of a child, loss of income or a job, and traumatic events such as a death or illness. Impacts at the individual level included reduced headaches, improved appetite and weight management, increased energy, improved sleep, better self-efficacy, and improved concentration, which was reported to lead to increased economic opportunities. At the interpersonal level, participants noted a reduction in conflict, better conflict management and resolution, increased harmony with family and community members, and improved relationships with their partners and children. Perceived challenges included balancing the intervention with livelihoods, preference for traditional medicines, actual or anticipated side effects with medication (FLX), mental health stigma, major life events, and perceived inadequate counseling and challenges with providers. The findings demonstrate the potential of the SMART DAPPER intervention for depression and trauma-related disorder treatments and underscore the challenges and barriers that must be addressed when scaling similar interventions. Trial registration: ClinicalTrials.gov identifier: NCT03466346.